2015
DOI: 10.1159/000430289
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin Inhibits the Differentiation and Proliferation of Cancer Stem Cells Derived from Primary Osteosarcoma Cells through Mir-148a

Abstract: Background/Aims: Osteosarcoma (OS) is the second leading cause of cancer-related death in children and young adults. Chemoresistance is the most important cause of treatment failure in OS, largely resulting from presence of cancer stem cells (CSCs). However, CSCs isolated from cancer cell lines do not necessarily represent those from primary human tumors due to accumulation of genetic aberrations that increase with passage number. Therefore, studies on CSCs from primary OS may be more important for understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…Bufalin exerts anticancer effects primarily by inhibiting tumor cell proliferation, inhibiting migration, inducing tumor cell apoptosis, and inducing differentiation [21]. One study reported that bufalin inhibits the differentiation and proliferation of CSCs derived from primary osteoscarcoma cells through miR-148a [22]; thus, microRNA expression may be affected by bufalin and may control the mechanism of action in tumors. However, the effect of bufalin on glioma cells and the underlying molecular mechanism of such an effect has yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Bufalin exerts anticancer effects primarily by inhibiting tumor cell proliferation, inhibiting migration, inducing tumor cell apoptosis, and inducing differentiation [21]. One study reported that bufalin inhibits the differentiation and proliferation of CSCs derived from primary osteoscarcoma cells through miR-148a [22]; thus, microRNA expression may be affected by bufalin and may control the mechanism of action in tumors. However, the effect of bufalin on glioma cells and the underlying molecular mechanism of such an effect has yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing studies have demonstrated that bufalin could inhibit cell proliferation and induce apoptosis in a variety of tumor cells [15-22]. However, the detailed mechanisms of bufalin-induced apoptosis in NSCLC cells have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs regulate the protein translation via its base-pairing with the 3′-untranslated region (3′-UTR) of the mRNA of the target genes to affect cell proliferation, apoptosis and differentiation [26,27,28]. MiRNAs have been well defined as a regular for tumorigenesis [29,30,31,32,33,34,35]. Among all miRNAs, miR-21 was recently reported as an aberrantly expressed miRNA in NSCLC [36,37,38,39,40], but the alteration of miR-21 during the Carboplatin treatment is not well defined.…”
Section: Introductionmentioning
confidence: 99%